HUBUNGAN INKOMPATIBILITAS GOLONGAN DARAH ABO DENGAN KEJADIAN JAUNDICE PADA NEONATUS - Chrisnoventa Veneranda; Fransisca Chondro (Bahasa Indonesia, 2023)
Neonatal jaundice or icterus is one of the health problems occured in newborns. Roughly 60% of infants born mature and 80% of infants born prematurely developed jaundice in the first week of their life. Neonatal jaundice is a condition caused by the accumulation of bilirubin in mucouse membrane and skin of the newborn with a discoloration of the skin and sclera as the symptoms. This issue is due to high levels of circulating bilirubin which is also known as hyperbilirubinemia. One of etiology of jaundice is the incompatibility of the blood types of the mother and child. Until now, studies related to maternal blood group incompatibility and the occurrence of jaundice in infants still give contradictory results. The aim of this study was to determine the relationship between ABO blood group incompatibility and the incidence of jaundice in neonates. This study used a cross-sectional design. The subject selection used non-probability sampling, and data from medical records of 110 newborns collected from December 2020 to December 2021. The inclusion criteria of this study were all infants born aterm at Budhi Asih Hospital, and the exclusion criteria were all infants, with asphyxia, hypoxia as well as mothers with preeclampsia. It was found that 82% of infants were diagnosed with neonatal jaundice and had blood group incompatibility. The chi-square test results showed a significant relationship between ABO blood group incompatibility and the incidence of neonatal jaundice (p = 0,002). There is a statistically significant relationship between ABO blood group incompatibility and the incidence of jaundice in neonates.